Yield and Extraction Rate Analysis of Phytochemical Compounds from Eucheuma cottonii, Ganoderma lucidum, and Gracilaria sp. using Subcritical Water Extraction - Fesa Putra Kristianto; Siti Machmudah; Sugeng Winardi; Wahyudiono; Motonobu Goto (ASEAN Journal of Chemical Engineering, 2021)
Eucheuma cottonii (E. cottonii), Ganoderma lucidum (G. lucidum), and Gracilaria sp. are plants that contain high phytochemicals, such as flavonoids, polyphenols, saponins, and tannins. In this work, the phytochemicals were obtained using the subcritical water extraction (SWE) process. The SWE method uses water as a solvent in subcritical conditions. Therefore, the SWE process is an environmentally friendly process for extraction. In order to run the SWE process optimally, measurement of the extraction rate of SWE is needed. Calculation of the extraction rate of SWE process used first and second-order models according to Lagergren equation. SWE process was started by setting temperatures from 140 to 180oC at a pressure of 7 MPa and solvent flow rate of 1 ml/min. Before starting the extraction, the raw material was loaded into the extractor. The raw materials used were E. cottonii, G. lucidum, and Gracilaria sp. The extraction process was carried out for 3 hours, and the product was collected every 30 minutes. The collected product was put into a sample bottle and dried using a freeze dryer. After that, the products obtained were balanced by an analytical scale. Based on the result, the optimum temperature for the SWE process was 180oC for E. cottonii and G. lucidum and 160oC for Gracilaria sp. The yields of the SWE process under the optimum temperature were 85.37%, 58.42%, and 75.73% for E. cottonii, G. lucidum, and Gracilaria sp, respectively. The extract contained phytochemical compounds detected by high-performance liquid chromatography analysis. The kinetics model of extraction rate for all variables exhibited a second-order kinetics model that indicated that the extraction process was influenced by more than one factor.